Recent insights on anti-dengue virus (DENV) medicinal plants : review on in vitro, in vivo and in silico discoveries - Sharoen Lim, Yu Ming; Jin Yu, Chieng; Yan, Pan (Taylor & Francis Online, 2020)
Dengue has become a global affliction despite continuous efforts to find cure for this age-old disease. Hopeful results for dengue vaccine are far-fetched as the effectiveness are tied to previous dengue virus (DENV) exposure and billions of dollars needed to be invested for vaccine development. Medicinal plants are ideal alternatives to combat DENV infection as it has long been utilized in traditional medicine besides showing virucidal properties. However, the mechanism of action by which the plant compounds inhibits the viral replication machinery remains to be discovered. This review provides existing knowledge on how DENV replicates within the host cells, recruiting more than 70 medicinal plants and some essential oils with anti-DENV properties, highlighting possible viral targets for DENV inhibition. The possible mechanism on how phytochemicals modulates host immune system in DENV infection by inhibiting cytokine storm and vascular leakage, were also discussed. Based on the in silico findings, NS2B/NS3 protease is the most distinctive DENV inhibitor target. Most anti-DENV plants research stood at their initial stages and efforts should be channeled into further in vitro characterization, in vivo studies by employing larger subsets of human subjects, and in silico studies to facilitate the understanding of inhibition mechanism.